An impossible object: on the analysis of the national phenomenon - Cruz Rodríguez, Edwin (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This paper presents a perspective of analysis of the nation as result of a hegemonic struggle between concrete subjects with diverse and antagonistic projects of nation. First analyzes the main forms like has argued the category of nation indicating the limits that they present for the comprehension of the phenomenon and, secondly, it reconstructs the perspective of analysis of the nation as hegemonic struggle. More than a transcendent essence or a set of tangible features, the nation is a historical construction and artificial result of specific power relations. Consequently, the analysis should focus on the struggle between national projects, played by specific subjects, competing by giving it meaning and become hegemonic.
Keywords: nation; hegemonic struggle; historicity; projects of nation